2009
DOI: 10.1007/s12600-009-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of botanical extracts on the biological activity of granulosis virus against Pieris brassicae

Abstract: A granulosis virus strain infecting Pieris brassicae (PbGV) was isolated from the dry temperate region of northwestern Himalayas as a potential microbial agent for its management. The effect of different botanicals (having insecticidal action against P. brassicae) on the bioefficacy of PbGV was evaluated under laboratory conditions using leaf disc bioassays on cabbage for improving the insecticidal performance of the PbGV. The synergistic action of different botanical extracts was evident in terms of reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…This may be due to the less developed defense system of insects at their young stage than at the older stage and greater permeability of the midgut peritrophic membrane, which allows the viral particles to enter and infect the susceptible cells causing virosis in the insect. These results are in line with the findings of Matthews et al (2002), Grzywacz et al (2008), and Bhandari et al (2009) in Lacanobia oleracea, Spodoptera exempta, and P. brassicae, respectively, who have also reported that early instar larvae were more susceptible than the late instar larvae to GVs, i.e., susceptibility is inversely proportional to the age of the insect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be due to the less developed defense system of insects at their young stage than at the older stage and greater permeability of the midgut peritrophic membrane, which allows the viral particles to enter and infect the susceptible cells causing virosis in the insect. These results are in line with the findings of Matthews et al (2002), Grzywacz et al (2008), and Bhandari et al (2009) in Lacanobia oleracea, Spodoptera exempta, and P. brassicae, respectively, who have also reported that early instar larvae were more susceptible than the late instar larvae to GVs, i.e., susceptibility is inversely proportional to the age of the insect.…”
Section: Discussionsupporting
confidence: 92%
“…The isolate has been tested against the pest alone and in combination with various botanical extracts under laboratory and field conditions (Bhandari et al 2009;Sood et al 2011) and found effective against the pest; however, the efficacy of the virus still requires further improvements for its successful field utilization owing to the above limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Pajmon (1999) listed 38 insect pest species that feed on the cole crops; among these the cabbage butterfly, Pieris brassicae (L.), is one of the most destructive pests, causing damage at all host plant growth stages from seedling to vegetative and flowering stages (Lal and Ram 2004;Younas et al 2004;Hasan 2008). It is an oligophagous pest with a wide host range and is known to infest 83 species of food plants belonging to Cruciferae (Bhandari et al 2009). It has a Palearctic distribution from North Africa across Europe and Asia to the Himalayan Mountains (Jainulabdeen and Prasad 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In India, it passes winter in the plains and migrates to hilly regions during summer (Gupta 1984). The young caterpillars feed gregariously on host plants' leaves (Younas et al 2004;Jainulabdeen and Prasad 2004;Hasan 2008;Bhandari et al 2009). On cabbage and cauliflower, the caterpillar sometime bores into the heads causing extensive damage and yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Fazil Hasan ( ) Email: fazilento10@gmail.com Fax: +91-9259167918 growing stages (seedling, vegetative, and flowering) (Gangwar 1980;Siraj 1999;Lal and Ram 2004;Sachan and Younas et al 2004;Hasan 2008;Bhandari 2009). Females lay batches of eggs on their host plant in the spring.…”
Section: Introductionmentioning
confidence: 99%